Magnetic storm and term‐day observations at the Prague observatory Clementinum in the mid‐19th century. Issue 1 (27th December 2021) - Hejda, Pavel; Revallo, Miloš; Valach, Fridrich
Abstract: Magnetic observations at the Clementinum Observatory were started in July 1839 and data up to 1917 were published in yearbooks. In addition to regular daily observations with a typical 2‐hr time step, two categories of data with a higher cadence were provided in the first decade. The first category captures 73 magnetic storms with their magnitude being of at least a moderate level. The second category is the dense observations during the days that had been agreed for joint measurements by the observatories organized in the Göttingen Magnetic Union (GMU), these measurements being known as term‐day observations. Whereas four terms per year were set by GMU, many observatories agreed to carry out additional observations in the eight remaining months. The term‐day observations also continued being performed for several years after the end of the GMU activities in 1841. Data of 120 term days from January 1840 to December 1849 were published. The declination was observed using the magnetic compass principle, while a bifilar apparatus was used to measure the horizontal intensity. When converting the data to the physical units of the SI, we have achieved the consistency of these high cadence data with previously published regular hourly observations of the geomagnetic field. This requirement was also met by considering the temperature dependence of measurements by the bifilar apparatus in determining the absolute values of horizontal intensity. Revealing the historical observations of the geomagnetic field can serve as a valuable material for studying the space weather in the past and may also contribute to the refinement of global field modelling. Abstract : Two categories of high cadence historical geomagnetic data from Clementinum observatory are presented in consistent forms and in proper physical units. The first category captures 73 magnetic storms with their magnitude being of at least a moderate level. The second category is the dense observations during the days that had been agreed for joint measurements by the observatories organised in the Göttingen Magnetic Union, these measurements being known as term‐day observations.